The Relationship Between Empowering Motivational Climate in Physical Education and Social Responsibility of High School Students: Chain Mediating Effect Test - Guo, Ke-lei; Ma, Qi-shuai; Yao, Shu-jun; Liu, Chao; Hui, Zhen (Frontiers in Psychology, 2022)
Objective:This study aimed to contribute to understanding the mechanisms underlying the association between empowering motivational climate in physical education and social responsibility among high school students,and have important implications for interventions aimed at improving social responsibility among high school students. Methods: Through the quota sampling,802 students(average age=17 years,SD=0.97 years) that complied with the requirements were surveyed from Anhui Province in China.Empowering motivational climate in physical education,social responsibility,interpersonal disturbance and general self-efficacy were assessed using standard scales.For data analysis,Pearson’s correlation analysis,structural equation model test,and bias-corrected percentile Bootstrap method were carried out in turn. Results: (1) Common method biases can be accepted in this study,and the correlation among empowering motivational climate in physical education,social responsibility,interpersonal disturbance and general self-efficacy are all significant;(2)Empowering motivational climate in physical education,interpersonal disturbance and general self-efficacy can all predict social responsibility significantly;(3)Structural equation modeling indicates good fit:χ²/df=2.86,RMESA=0.068,CFI=0.92,NNFI=0.91,NFI=0.90,GFI=0.93.It indicates that interpersonal disturbance and general self-efficacy can play mediating roles between empowering motivational climate in physical education and social responsibility respectively.After that,interpersonal disturbance as well as general self-efficacy in turn plays the chain mediating effect in the relationship between empowering motivational climate in physical education and social responsibility.The effect size of the mediating effect of interpersonal disturbance and general self-efficacy in the relationship between empowering motivational climate in physical education and social responsibility is 0.048 and 0.148 respectively,and the effect size of the chain mediating effect is 0.031. Conclusion:Empowering motivational climate in physical education not only has a direct effect on social responsibility among high school students,but also influences social responsibility by the chain mediating effect of interpersonal disturbance and general self-efficacy.